Oxoiron(v) mediated selective electrochemical oxygenation of unactivated C–H and CC bonds using water as the oxygen source. Issue 43 (14th October 2020) - Chandra, Bittu; K. M., Hellan; Pattanayak, Santanu; Gupta, Sayam Sen
Abstract : A biomimetic iron complex-mediated selective and efficient electrochemical oxygenation of unactivated C–H bonds and CC bonds using water as an O-atom source. Abstract : An efficient electrochemical method for the selective oxidation of C–H bonds of unactivated alkanes (BDE ≤97 kcal mol −1 ) and CC bonds of alkenes using a biomimetic iron complex, [(bTAML)Fe III -OH2 ] −, as the redox mediator in an undivided electrochemical cell with inexpensive carbon and nickel electrodes is reported. The O-atom of water remains the source of O-incorporation in the product formed after oxidation. The products formed upon oxidation of C–H bonds display very high regioselectivity (75 : 1, 3° : 2° for adamantane) and stereo-retention (RC ∼99% for cyclohexane derivatives). The substrate scope includes natural products such as cedryl acetate and ambroxide. For alkenes, epoxides were obtained as the sole product. Mechanistic studies show the involvement of a high-valent oxoiron(v ) species, [(bTAML)Fe V (O)] − formed via PCET (overall 2H + /2e − ) from [(bTAML)Fe III -OH2 ] − in CPE at 0.80 V ( vs. Ag/AgNO3 ). Moreover, electrokinetic studies for the oxidation of C–H bonds indicate a second-order reaction with the C–H abstraction by oxoiron(v ) being the rate-determining step.